2005
DOI: 10.1124/jpet.105.084855
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Stimulation of Amylase Secretion from Pancreatic Acinar Cells Studied with Muscarinic Acetylcholine Receptor Mutant Mice

Abstract: Muscarinic acetylcholine receptors (mAChRs) expressed by pancreatic acinar cells play an important role in mediating acetylcholine-dependent stimulation of digestive enzyme secretion. To examine the potential roles of M 1 and M 3 mAChRs in this activity, we used M 1 and M 3 receptor single knockout (KO) and M 1 /M 3 receptor double KO mice as novel experimental tools. Specifically, we examined the ability of the muscarinic agonist carbachol to stimulate amylase secretion in vitro, using dispersed pancreatic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 37 publications
1
38
2
Order By: Relevance
“…A small amount of M 1 receptors (Wall et al, 1991) and mRNA (Maeda et al, 1988) has been detected in wild-type intestinal smooth muscle from rats, which could account for the muscarinic phosphoinositide response observed here. No compensatory increases in muscarinic receptor expression have been detected in muscarinic receptor knockout mice (Gautam et al, 2005), and evidence for a decrease in expression has actually been observed in brain (Oki et al, 2005). It would be difficult to ascribe potential changes in other signaling proteins in M 2 /M 3 knockout mice to the small M 1 response that we observed.…”
Section: Discussioncontrasting
confidence: 43%
“…A small amount of M 1 receptors (Wall et al, 1991) and mRNA (Maeda et al, 1988) has been detected in wild-type intestinal smooth muscle from rats, which could account for the muscarinic phosphoinositide response observed here. No compensatory increases in muscarinic receptor expression have been detected in muscarinic receptor knockout mice (Gautam et al, 2005), and evidence for a decrease in expression has actually been observed in brain (Oki et al, 2005). It would be difficult to ascribe potential changes in other signaling proteins in M 2 /M 3 knockout mice to the small M 1 response that we observed.…”
Section: Discussioncontrasting
confidence: 43%
“…CCK-8 or CCh induced PKD1 phosphorylation and activation at the concentration as low as 0.1 nM or 1 M, respectively, a physiological level of CCK-8 or CCh that causes maximal digestive enzyme secretion. The maximal effects of these agonists on PKD1 were achieved at 10 -100 nM CCK-8 or at 100 -1,000 M CCh, i.e., at their supramaximal concentrations that cause inhibition of enzyme secretion and activation of the inflammatory response (2,8,9,51). These results indicate that PKD1 is activated by CCK-8 and CCh at both physiological and pathological doses.…”
Section: Cck-8 and Cch Induce Both Pkd1 Phosphorylation/activation Anmentioning
confidence: 52%
“…Elevated FEV, TPH1, and SLC6A4 expression suggests PP/ gamma cells share a suite of characteristic genes with serotonergic neurons that, in the pancreas, integrate central and peripheral hunger and satiety cues. We also observed high PP/gamma expression of muscarinic acetylcholine receptor M3, CHRM3, which stimulates exocrine pancreatic amylase (Gautam et al 2005), insulin secretion (Kong and Tobin 2011;Molina et al 2014), and smooth muscle contraction and gastric emptying (Eglen et al 1994). These data implicate the less abundant delta and PP/gamma cell types as critical for islet function via the integration of systemic cues and warrant further studies to elucidate the function and health of these cells in normal and diabetogenic conditions.…”
Section: Fevmentioning
confidence: 58%